Evaluating the Usability of Moodle-based Learning Management System Application in Faculty of Engineering UNSIKA Using USE Questionnaire - Pambudi, Teguh; Umam, Hilman Imadul; Armin, Edmund Ucok (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2023)
A Moodle-based LMS has been used by the Faculty of Engineering Universitas Singaperbangsa Karawang to support blended learning. Therefore, it needs to be evaluated in terms of user satisfaction and usability. The USE Questionnaire was used in this study to evaluate Moodle-based LMS usability. The usability was evaluated by analyzing the data from the USE Questionnaire, which was personally filled out by 167 respondents, both students and lecturers. The result showed that USE Questionnaire used in this study possessed excellent validity and reliability with coefficient values above 0.700 and 0.981 respectively. In addition, the percentage of each usability parameter for Moodle-based LMS application was as follows: 70,1% of usefulness, 68,9% ease of use, 73,7% ease of learning, and 67,9% of satisfaction. It can be concluded that this application is worthy to use.